Data mining techniques for predicting the consumer behavior based on government utility water services - Kaladgi, Bindu; Sumanta, Guha; Phan, Minh Dung; Bohez, Erik L.J.; Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2017)
The process of classifying through huge chunks of data sets in order to {uFB01}nd out patterns and develop relationships to solve issues by data analysis is known as data mining. Data mining tools allow enterprises to predict future trends.Data mining refers to extracting knowledge from large amount of data.There are number of data mining techniques like clustering , decision trees,multiple predictive models. Here , we discuss the techniques of data mining in current practice which would be considered important to understand consumer behavior. Research study contains of 2 models which are associated to one another one being water services provided by the govt and the other being behavior of the consumer or customer track ,a study is conducted out to perceive the purchase of consumers and the procedure of utilization behaviour and to foster the customer research study and services their motive, and the other one being to collect apt information about customers. Govt looks for the supply of water to the household and sewerage services of the city , the services include supply of potable drinkingwater,sewage disposal and treatment, designing, outlining and execution of water supply and sewage works. To have knowledge of customers {uFB01}rst choice construction processes and their connected conduct is fundamental for government to cultivate pro{uFB01}table goods or help and for policy makers to prosper favorable policies. consumers buying behaviour targets on how social and commercial marketing can expect and react to behaviour of consumer.The main goal is useful for government in order to improve the water services provided according to the consumer behavior track and also for researches to get an comprehensive view of the literature in this {uFB01}eld.
A research submitted in partial fulfillment of the requirements for the degree of Master of Science in Information Management, School of Engineering and Technology
Research studies project report (M. Sc.) - Asian Institute of Technology, 2017
Keywords: Data mining -- Computer programs; Consumer behavior -- Data processing; Water utilities -- Government policy